Myth, mind, and the screen : understanding the heroes of our times - Izod, John, 1940- (Cambridge studies in criminology (Cambridge University Press), 2001)
Myth, Mind and the Screen is a systematic attempt to apply Jungian theory to the analysis of films (including 2001: A Space Odyssey, The Silence of the Lambs and The Piano) as well as a variety of cultural icons and products such as Madonna, Michael Jackson and televised sport.